2020
DOI: 10.3390/biomedicines8080288
|View full text |Cite
|
Sign up to set email alerts
|

Gene Regulatory Network Analysis of Perivascular Adipose Tissue of Abdominal Aortic Aneurysm Identifies Master Regulators of Key Pathogenetic Pathways

Abstract: The lack of medical therapy to treat abdominal aortic aneurysm (AAA) stems from our inadequate understanding of the mechanisms underlying AAA pathogenesis. To date, the only available treatment option relies on surgical intervention, which aims to prevent AAA rupture. Identifying specific regulators of pivotal pathogenetic mechanisms would allow the development of novel treatments. With this work, we sought to identify regulatory factors associated with co-expressed genes characterizing the diseased perivascul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 66 publications
0
16
0
Order By: Relevance
“…Our KEGG pathway analysis revealed that miR-30c-1-3p targets were enriched in the axonal guidance, thyroid hormone signaling, and MAPK signaling pathways. Indeed, previous studies indicate that the MAPK pathway is the key biochemical mechanism involved in AAA [17]. Furthermore, MMP-9, one of the main mir-30c-1-3p targets, has been reported to contribute to the rupture of AAAs [18], whereas MMP-9 plasma concentrations are positively correlated with the AAA growth rate [19] and AAA rupture [20,21].…”
Section: Discussionmentioning
confidence: 99%
“…Our KEGG pathway analysis revealed that miR-30c-1-3p targets were enriched in the axonal guidance, thyroid hormone signaling, and MAPK signaling pathways. Indeed, previous studies indicate that the MAPK pathway is the key biochemical mechanism involved in AAA [17]. Furthermore, MMP-9, one of the main mir-30c-1-3p targets, has been reported to contribute to the rupture of AAAs [18], whereas MMP-9 plasma concentrations are positively correlated with the AAA growth rate [19] and AAA rupture [20,21].…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence of increased GSK3β phosphorylation in abdominal aortic aneurysms (AAA) (Krishna et al, 2017). GSK3β was also identified as a likely regulator of pathogenic mechanisms from analysis of perivascular adipose tissue of patients with AAA (Piacentini et al, 2020). Here, we demonstrated that GSK3β inhibition was beneficial in our iPSC-derived MFS VSMCs using both multiple SMIs and a genetic approach.…”
Section: Discussionmentioning
confidence: 99%
“…They described that significantly expressed genes were enriched in this GO term [ 41 ]. Another study showed that the mitotic cell cycle was also significantly associated with dilated aortic perivascular adipose tissue [ 16 ]. The most enriched pathway of the blue module in KEGG was fluid shear stress and atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%
“…Although the inherent pathology of aneurysm is different between mice and humans, it shares some of the important properties of human AAA, like pronounced inflammatory responses and aortic rupture [11][12][13][14][15]. Based on the findings from mouse models and human samples, AAA is currently accepted as an inflammationdriven disease, as many related processes (such as infiltration of macrophages, neutrophils, B cells and T cells, and activation of inflammatory pathways) were found both in humans and mice [16][17][18][19]. Overactivation of the inflammatory response leads to the destruction of aortic media through the release of proteolytic enzymes and the death of vascular smooth muscle cells, which further promote AAA development [20].…”
Section: Introductionmentioning
confidence: 99%